2007
DOI: 10.1007/s00421-007-0567-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged recombinant human erythropoietin administration on muscle membrane transport systems and metabolic marker enzymes

Abstract: Adaptations to chronic hypoxia involve changes in membrane transport proteins. The underlying mechanism of this response may be related to concomitant occurring changes in erythropoietin (Epo) levels. We therefore tested the direct effects of recombinant human erythropoietin (rHuEpo) treatment on the expression of muscle membrane transport proteins. Likewise, improvements in performance may involve upregulation of metabolic enzymes. Since Epo is known to augment performance we tested the effect of rHuEpo on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
2
15
0
1
Order By: Relevance
“…In partial agreement with the thermogenesis theory suggested by the authors, we have previously reported higher uncoupled mitochondrial respiration in the same participants included in the present investigation (Plenge et al, 2012). On the contrary, some other studies have not found any effect of prolonged erythropoietin administration on muscle hexokinase or membrane transport system levels (Juel, Thomsen, Rentsch, & Lundby, 2007), erythropoietin receptormediated signalling cascades (Christensen, Lundby, et al, 2012), muscle phenotype and angiogenesis (Lundby, Hellsten, Jensen, Munch, & Pilegaard, 2008), suggesting that the effects of erythropoietin on skeletal muscle are likely indirect, i.e., through increased oxygen delivery. The results obtained from this investigation cannot rule out a possible indirect effect of erythropoietin on the skeletal muscle by means other than erythropoietin receptor, and further research is needed to elucidate the intracellular mechanisms responsible for the higher mitochondrial fat oxidation capacity observed.…”
supporting
confidence: 92%
“…In partial agreement with the thermogenesis theory suggested by the authors, we have previously reported higher uncoupled mitochondrial respiration in the same participants included in the present investigation (Plenge et al, 2012). On the contrary, some other studies have not found any effect of prolonged erythropoietin administration on muscle hexokinase or membrane transport system levels (Juel, Thomsen, Rentsch, & Lundby, 2007), erythropoietin receptormediated signalling cascades (Christensen, Lundby, et al, 2012), muscle phenotype and angiogenesis (Lundby, Hellsten, Jensen, Munch, & Pilegaard, 2008), suggesting that the effects of erythropoietin on skeletal muscle are likely indirect, i.e., through increased oxygen delivery. The results obtained from this investigation cannot rule out a possible indirect effect of erythropoietin on the skeletal muscle by means other than erythropoietin receptor, and further research is needed to elucidate the intracellular mechanisms responsible for the higher mitochondrial fat oxidation capacity observed.…”
supporting
confidence: 92%
“…Furthermore, over-expression of Epo in mice skeletal muscle tissue lead to up-regulation of genes involved in lipid metabolism while genes involved in glucose metabolism were down-regulated [37]. In contrast, 13 weeks of treatment with rHuEpo in humans did not lead to changes in levels of either hexokinase or cytochrome c [16].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have investigated changes in mRNA levels of pertinent proteins and structural changes in muscle after recombinant human Epo (rHuEpo) administration with conflicting results [13], [16], [17]. Thus, even though the Epo-R has been identified in human skeletal muscle tissue, its role remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The data support the assumption that rHuEpo might evoke its effect independently from nerve regeneration in the graft by acting directly on the muscle or the neuromuscular junction. EpoR has recently been discovered in skeletal muscle and systemic rHuEpo treatment has shown to affect the expression of skeletal muscle proteins in vivo [27]. The fact that we did not detect reduced muscle atrophy in the conduit groups could imply that beginning re-innervation is needed for rHuEpo to render its supporting effect.…”
Section: Discussionmentioning
confidence: 87%